5′RUNX1-3′USP42 chimeric gene in acute myeloid leukemia can occur through an insertion mechanism rather than translocation and may be mediated by genomic segmental duplications - Zagaria, Antonella (BioMed Central, 2014)
BACKGROUND: The runt-related transcription factor 1 (RUNX1) gene is a transcription factor that acts as a master regulator of hematopoiesis and represents one of the most frequent targets of chromosomal rearrangements in human leukemias. The t(7;21)(p22;q22) rearrangement generating a 5′RUNX1-3′USP42 fusion transcript has been reported in two cases of pediatric acute myeloid leukemia (AML) and further in eight adult cases of myeloid neoplasms. We describe the first case of adult AML with a 5′RUNX1-3′USP42 fusion gene generated by an insertion event instead of chromosomal translocation. METHODS: Conventional and molecular cytogenetic analyses allowed the precise characterization of the chromosomal rearrangement and breakpoints identification. Gene expression analysis was performed by quantitative real-time PCR experiments, whereas bioinformatic studies were carried out for revealing structural genomic characteristics of breakpoint regions. RESULTS: We identified an adult AML case bearing a ins(21;7)(q22;p15p22) generating a 5′RUNX1-3′USP42 fusion gene on der(21) chromosome and causing USP42 gene over-expression. Bioinformatic analysis of the genomic regions involved in ins(21;7)/t(7;21) showed the presence of interchromosomal segmental duplications (SDs) next to the USP42 and RUNX1 genes, that may underlie a non-allelic homologous recombination between chromosome 7 and 21 in AML. CONCLUSIONS: We report the first case of a 5′RUNX1-3′USP42 chimeric gene generated by a chromosomal cryptic insertion in an adult AML patient. Our data revealed that there may be a pivotal role for SDs in this very rare but recurrent chromosomal rearrangement.